Hope to cope with Covid-19 - Dr. Ruth Sneha C (Journal of Clinical and Biomedical Sciences)
The novel Corona virus pandemic as de-clared by the World Health Organisation (WHO) has brought in front of us many challenges in all aspects of life. It is an event that most of us have not wit-nessed anytime in our lives. Although social distanc-ing, quarantine and self-isolation are essential to prevent spread of this highly virulent disease, an atmosphere of fear and anxiety is built up. So it is at these times that we have to improve our mental and emotional wellbeing